1991
DOI: 10.1073/pnas.88.3.732
|View full text |Cite
|
Sign up to set email alerts
|

Sequence requirement for peptide recognition by rat brain p21ras protein farnesyltransferase.

Abstract: We tested 42 tetrapeptides for their ability to bind to the rat brain p2l' protein farnesyltransferase as estimated by their ability to compete with p2lH"-in a farnesyltransfer assay. Peptides with the highest affinity had the structure Cys-Al-A2-X, where positions Al and A2 are occupied by aliphatic amino acids and position X is-occupied by a COOHterminal methionine, serine, or phenylalanine. Charged residues reduced affinity slightly at the Al position and much more drastically at the A2 and X positions. Eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
212
0
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(228 citation statements)
references
References 25 publications
(26 reference statements)
14
212
0
1
Order By: Relevance
“…Commonly, proteins such as LKB1, were X is a glutamine residue, are farnesylated [15]. In general, A " and A # are aliphatic amino acids ; however, peptide studies have shown that most residues are tolerated in the A " position [31]. Other proteins, like LKB1, which have a basic residue in the A1 position and are known to be prenylated, include hepatitis delta virus large antigen (CRPQ) [32] and RhoB (CKVL) [33].…”
Section: Functional Prenylation Motif Contained Within the C-terminalmentioning
confidence: 99%
“…Commonly, proteins such as LKB1, were X is a glutamine residue, are farnesylated [15]. In general, A " and A # are aliphatic amino acids ; however, peptide studies have shown that most residues are tolerated in the A " position [31]. Other proteins, like LKB1, which have a basic residue in the A1 position and are known to be prenylated, include hepatitis delta virus large antigen (CRPQ) [32] and RhoB (CKVL) [33].…”
Section: Functional Prenylation Motif Contained Within the C-terminalmentioning
confidence: 99%
“…Nascent CAAX proteins are synthesized in the cytosol where they encounter one of two protein prenyltransferases that modify the CAAX cysteine by thioether linkage of a C-15 farnesyl or C-20 geranylgeranyl lipid (Clarke, 1992;Casey and Seabra, 1996). The substrate specificity for farnesyltransferase versus geranylgeranyltransferase type I (GGTase I) is determined by the residue in the X position of the CAAX motif: S or M specifies farnesylation, whereas L specifies geranylgeranylation (Moores et al, 1991;Reiss et al, 1991). Although Ras family proteins are farnesylated, most Rho family proteins are geranylgeranylated.…”
Section: Introductionmentioning
confidence: 99%
“…Ras prenylation is thought to facilitate membrane targeting and to be essential for Ras function (Kato et al, 1992). In addition, this modi®cation can have important consequences for protein-protein interactions (Glomset and Farnsworth, 1994;Reis et al, 1991;James et al, 1995). Prenylated H-Ras and NRas proteins can be further lipidated by palmitoylation.…”
Section: Introductionmentioning
confidence: 99%